Elevated LIF and JAK-STAT activation drive severe COVID-19 in myeloma patients receiving the BCMA-CD3 bispecific antibody Elranatamab - Ziping Li; Fujing Zhang; Xianghong Jin; Junling Zhuang (Journal of Translational Medicine)
Abstract Background Immunotherapy is a significant risk factor for severe COVID-19 in multiple myeloma (MM) patients. Understanding how immunotherapies lead to severe COVID-19 is crucial for improving patient outcomes. Methods Human protein microarrays were used to examine the expression of 440 protein molecules in MM patients treated with bispecific T-cell engagers (BiTe) (n = 9), anti-CD38 monoclonal antibodies (mAbs) (n = 10), and proteasome inhibitor (PI)-based regimens (n = 10). Differentially expressed proteins (DEPs) were identified and analyzed using bioinformatics. Results BiTe therapy was associated with a higher incidence of severe COVID-19. We identified 21 and 29 DEPs between BiTe and anti-CD38 mAbs group, and BiTe and PI-based group, respectively, along with 25 DEPs between the anti-CD38 and PI groups. Principal component analysis and clustering showed distinct protein expression profiles between the BiTe and PI groups. Gene Ontology (GO) analysis revealed that DEPs between the BiTe and PI groups were related to cytokine activity and leukocyte migration. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that these DEPs were enriched in cytokine-cytokine receptor interaction and JAK-STAT signaling pathways. Leukemia inhibitory factor (LIF) is the most correlated with other DEPs and thus may play a key role in both enriched pathways, and the level of LIF protein was highest in the BiTe group. Conclusions BiTe therapy is linked to a higher risk of severe COVID-19 due to an inflammatory cytokine storm, with LIF and the JAK-STAT pathway playing key roles. Targeting LIF and JAK-STAT pathway may help reduce severe COVID-19 in MM patients treated with BiTe.